Manufacturing and analysis of carbon fiber knee ankle foot orthosis - M. Takhakh, Ayad; M. Abbas, Saif (International Journal of Engineering and Technology, 2018)
Knee ankle foot orthoses (KAFOs) are used by paraplegia patients with low level spinal cord injury and having well control of the stem muscles. Four layers of carbon fiber with C- orthocryl lamination resin are used for manufacturing the knee ankle foot orthoses in this work. The mechanical properties of most of the components materials were estimated with the aid of fatigue and tensile test machines. Results of the tensile tests showed that the mechanical properties: yield stress, ultimate strength and modulus of elasticity were 92MPa, 105.7MPa and 2GPa respectively. The value of amidst pressure between the patient limb and the manufactured KAFO was measured using (F-socket) Mat scan sensor and these values of pressure were (663kPa) and (316kPa) for the thigh and calf regions respectively.Â
Keywords: KAFO; Carbon Fiber; Tensile Test and Interface Pressure